1990
DOI: 10.1111/j.1365-2923.1990.tb02654.x
|View full text |Cite
|
Sign up to set email alerts
|

Televised paediatric consultations: a student evaluation of a multipurpose learning strategy

Abstract: Since 1984, each student in the sixth-year paediatric rotation in the Department of Paediatrics and Child Health at the University of the Witwatersrand has been videotaped while undertaking a comprehensive paediatric primary care consultation. Video replay of the consultation by each individual student was evaluated by the student together with medical and social work tutors. This incorporated psychosocial aspects, communication skills, doctor-mother-child interactions, as well as essential medical content, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Fourteen out of these 16 studies reported that video review was a useful learning aid. Many of these studies reported high student satisfaction with video review 61–65. Two studies also reported an improvement in interviewing skills after video review and feedback 33,66.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen out of these 16 studies reported that video review was a useful learning aid. Many of these studies reported high student satisfaction with video review 61–65. Two studies also reported an improvement in interviewing skills after video review and feedback 33,66.…”
Section: Resultsmentioning
confidence: 99%